Artengemeinschaften benthischer Foraminiferen in der Laptev-See, sibirische Arktis: Rezente Verteilungsmuster und Ökologie - Bude, Sven-Ole (1997)
During the TRANSDRIFT I expedition aboard the icebreaker "IVAN KIREYEV" to the Laptev Sea (northern Siberia, Arctic Ocean) in 1993, 32 surface samples of box corers were taken. In the surface samples 43 species of benthic foraminifer and one species of planktic foraminifera were determined. The benthic foraminifera fauna was found to be low divers and dominated by agglutinated foraminifera. According to the abundances and the diversities the Laptev Sea can be divided into three different areas; the north-eastern, south-eastern and western Laptev Sea. In the western Laptev Sea the highest abundances with up to 5200 specimens/100 g and the highest diversities are found, while the lowest abundances (up to 220 Ind./100 g) and lowest diversities (up to 1.8) occur in the south-eastern part of the Laptev Sea in the area of the main outflow of the Lena- and Yana rivers. The good preservation of the calcareous benthic foraminifera and the few broken specimens led to the conclusion that the calcite dissolution is not of great importance in the Laptev Sea shelf area. The performed statistical analysis of the fauna showed that there is a close relationship between the faunas and the depth. This could be caused by riverine water in parts which are shallower and nearer to the land, as well as by the effect of "ice gouging" of icebergs in the deeper parts of the Laptev Sea.